Dependence of plasminogen activator inhibitor-1 level on -675 4G/5G polymorphism in PAI-1 gene in patients with traumatic brain injury - Potapov Jr, Oleksandr; Kmyta, Oleksii (Ukrainian Neurosurgical Journal, 2014)
The purpose. To study relationship between plasminogen activator inhibitor-1 (PAI-1) level in plasma and -675 4G/5G polymorphism in the PAI-1 gene in patients with traumatic brain injury (TBI) in dynamics of treatment. Materials and methods. The state of hemostasis in 200 patients with TBI was analyzed by means of studying relationship between PAI-1 level in plasma and -675 4G/5G polymorphism in the PAI-1 gene. Results. Correlation between PAI-1 level increasing and 4G/4G and 4G/5G genotype in patients was shown. PAI-1 level increasing in dynamics of treatment was found in patients with 4G/4G and 4G/5G genotypes. Conclusions. The relationship between -675 4G/5G polymorphism in the PAI-1 gene and PAI-1 level in plasma in patients with TBI was proved.